2007
DOI: 10.2224/sbp.2007.35.5.659
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between LMX and Subordinates' Feedback-Seeking Behaviors

Abstract: Relationships among subordinates' feedback-seeking strategy preferences, Leader-Member Exchange (LMX), social cost, and source credibility were examined. Employees (N = 134) of civil engineering companies in South Korea completed a questionnaire. Findings showed that LMX quality, social cost, and source credibility either independently or jointly influenced subordinates' feedback-seeking strategy preferences. LMX was positively related to preference for using direct strategies, but not significantly related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…The LMX model posits that leaders’ behaviours are not necessarily consistent across all subordinates (Lee et al. 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LMX model posits that leaders’ behaviours are not necessarily consistent across all subordinates (Lee et al. 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The LMX model posits that leaders' behaviours are not necessarily consistent across all subordinates (Lee et al 2007). Managers and supervisors are considered to develop close relationships with only a few subordinates, and these relationships are characterized by high quality exchanges (high level of LMX quality; Ellemers et al 2004, Epitropaki & Martin 2005.…”
Section: Introductionmentioning
confidence: 99%
“…One important variable that may moderate the leadership style–job performance relationship is the “leader-member dyadic interaction cultural configuration” in the workgroup. Said differently, we are referring to the degree to which the cultural configuration of workgroup members and their immediate supervisor is congruent (Gordon & Stewart, 2009; Lee, Park, Lee, & Lee, 2007).…”
mentioning
confidence: 99%
“…The chi-square difference test between the proposed model and the alternative model, Dw(1) ¼ 1.14, p > .05, indicated that the addition of the path did not significantly improve the overall fit of the model. Furthermore, we added a path from the relationship quality to willingness to take the mentor's advice as another alternative model on the basis of previous research that showed a positive relationship between the quality of relationship and advicetaking behaviors (e.g., feedback-seeking behaviors; Lee et al, 2007). The alternative model was found to fit the data, w 2 (135) ¼ 225.75, IFI ¼ .96; TLI ¼ .94; CFI ¼ .95; RMSEA ¼ .06.…”
Section: Proposed Model Testingmentioning
confidence: 99%